Pengaruh Gaya Kepemimpinan Transformasional dan Fasilitas Kerja terhadap Kinerja Aparatur Sipil Negara dengan Pengawasan Kerja Sebagai Variabel Intervening pada Biro Umum Sekretariat Daerah Provinsi Jambi - Hendarji, Hendarji; Suryani, Arna; Sudirman, Sudirman (Universitas Batanghari, 2024)
Transformational and work facilities on performance with work supervision as an intervening variable at the General Bureau of the Jambi Province Regional Secretariat. The method used in this research is descriptive and quantitative descriptive statistics. The research object in this study is the influence of transformational leadership style and work facilities on employee performance with work supervision as an intervening variable at the General Bureau of the Regional Secretariat of Jambi Province with a total of 91 specimens. This research uses the Smart PLS 3.0 analysis tool. Based on the reflection of the transformational leadership style, work facilities, supervision of activities and results of activities of employees of the General Bureau of the Regional Secretariat of Jambi Province, it shows that the transformational leadership style has a total score of 4366 in the good category. Then, for an overview of the work facilities variable, it shows that the work facilities at the General Bureau of the Regional Secretariat of Jambi Province are higher with a total score of 2499 in the very good category. Furthermore, the description of the work supervision variable shows a total score of 3449 with good criteria, while the reflection of objects resulting from the activities of the State Civil Service with a total score of 4495 is quite satisfactory. Based on the results of a study using the Smart PLS 3.0 application, transformational leadership style has a relevant impact on monitoring activities, work facilities have a relevant impact on monitoring activities, transformational leadership style has a positive and relevant impact on the activities of the State Civil Service, work facilities have a positive and relevant impact on the activities of the State Civil Apparatus, supervision has a good and relevant impact on the activities of the State Civil Service, transformational leadership style has a relevant impact on activities.